The Effect of Education with Video Media on Exclusive Breastfeeding on the Motivation of Pregnant Women at Wonodadi Health Center - Dwi Lukmawati; Fransiska Septiana; Lailaturohmah; Neta Ayu Andera (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Background: Exclusive breastfeeding is breastfeeding only to infants up to 6 months old without providing food except medicine. The scope of exclusive breastfeeding is still low due to several factors, one of which is knowledge and attitude. It is necessary to do counseling to improve knowledge and attitudes by using one of the media, namely video. Video is an audiovisual medium that stimulates more senses. Objective: Knowing the effect of using video media about exclusive breastfeeding on the motivation of pregnant women at the Wonodadi Health Center. Method: This type of research is quasi experiment with pre test-post test with control design. Results: The results of the study were obtained in the experimental group with video, Pvalue results 0.000 (< α) and in the control group using MCH books, Pvalue results 0.001 (< α). The odd ratio value shows that video media has a greater effect on the motivation of third trimester pregnant women regarding exclusive breastfeeding, which is 28 times higher than the MCH book, the motivation of mothers is only 15 times. Discussion: The motivation of third trimester pregnant women is higher when education is provided with video media because it is easier to understand, not monotonous, interesting images and clear sounds make mothers interested in participating. Conclusion: Based on the results of the study, it can be concluded that videos are more influential on increasing knowledge and attitudes compared to leaflets, so researchers recommend the use of videos as an alternative media in counseling about exclusive breastfeeding at the Wonodadi Health Center.